2011
DOI: 10.4067/s0718-95162011000100002
|View full text |Cite
|
Sign up to set email alerts
|

Water Requirements and Water Use Efficiency of Carrot Under Drip Irrigation in a Haploxerand Soil

Abstract: Water management efficiency is a key issue for sustainable agriculture development, since it is necessary to get a higher biomass production per unit of applied water. This study aimed to determine both water requirements and water use efficiency (WUE) and their effect on yield and quality parameters in carrots (Daucus carota L.), during the 2006 -2007 growing season in Chillán, Chile (36º 35' 43.2" S, 72º 04' 39" W, 140 m altitude). The water treatments applied were 25, 50, 75, 100 and 125 % pan evaporation (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 15 publications
(3 reference statements)
4
14
0
Order By: Relevance
“…In earlier growth stages, full irrigation can supply enough water to plants and thus maintain adequate turgor, which improves the development and growth of plant stem and branches (Shiri-e-Janagard et al 2009). Full irrigation permitted optimum transpiration and faster growth of the aerial parts (Quezada et al 2011;Khakbazan et al 2011). Application of HA further improved vegetative growth traits compared with the control plants (Table 1).…”
Section: Resultsmentioning
confidence: 98%
“…In earlier growth stages, full irrigation can supply enough water to plants and thus maintain adequate turgor, which improves the development and growth of plant stem and branches (Shiri-e-Janagard et al 2009). Full irrigation permitted optimum transpiration and faster growth of the aerial parts (Quezada et al 2011;Khakbazan et al 2011). Application of HA further improved vegetative growth traits compared with the control plants (Table 1).…”
Section: Resultsmentioning
confidence: 98%
“…Water use efficiency and water expanse efficiency was recorded the highest with irrigation by drip irrigation method (M 2 ) at 0.4 IW/CPE ratio followed by micro sprinkler method (M 1 ) at 0.4 IW/CPE ratio and the lowest Water expense efficiency and water use efficiency were recorded under surface irrigation method (M 3 ) and 1.0 IW/CPE ratios (Table 5). Quezada et al (2011) reported that, the lower water use efficiency at 1.2 IW/CPE and 100 per cent CPE might be due to a greater expense of water use and comparatively lower yield in carrot. This might be on account of ease with which moisture was available for crop growth due to more number of irrigations resulted in application of more quantity of water which enhanced the CU of water by luxuriant growing plant body which in turn increased the evapotranspiration losses.…”
Section: Effect Of Irrigation Methods On Growth and Yield Attributingmentioning
confidence: 99%
“…Soil moisture, fertilizer and temperature are important factors affecting plant growth and agricultural production (Quezada et al 2011;Hattori et al 2013). Soil moisture can play a vital role in the mineralization process of fertilizers and organic amendments, which release nutrients in soil for use by plants.…”
Section: Introductionmentioning
confidence: 99%